2020
DOI: 10.1002/pbc.28282
|View full text |Cite
|
Sign up to set email alerts
|

Supporting “good parent” beliefs with communication: Where do we go next?

Abstract: SISK interventions in oncology did not find any studies of interventions that specifically targeted pediatrics. 9 Now that we have such a rich body of descriptive literature, this field is ready to transition toward the development of interventions to improve communication. The remaining question is, "What kinds of interventions will best support clinicians to enact effective communication behaviors?" Knowledge is important, but often insufficient, to lead to behavioral change. Neither are good intentions enou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Previous research indicates that parents of medically complex, seriously, or terminally ill children develop a deeply personal definition of what it means to be a ''good parent'' to their child. [1][2][3][4][5][6][7][8][9][10][11][12] This definition is at once an identity and a goal and functions as a guiding compass for parents as they make medical decisions for their child, both small and large. 16 Respondents reported talking about their ''good parent'' beliefs with friends and loved ones as part of their processing of parental roles; most respondents indicated also wanting to explore these beliefs with the care provider(s) they know well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research indicates that parents of medically complex, seriously, or terminally ill children develop a deeply personal definition of what it means to be a ''good parent'' to their child. [1][2][3][4][5][6][7][8][9][10][11][12] This definition is at once an identity and a goal and functions as a guiding compass for parents as they make medical decisions for their child, both small and large. 16 Respondents reported talking about their ''good parent'' beliefs with friends and loved ones as part of their processing of parental roles; most respondents indicated also wanting to explore these beliefs with the care provider(s) they know well.…”
Section: Discussionmentioning
confidence: 99%
“…4 For care providers from all disciplines, understanding parental perspectives on how they aim to be ''good parents'' to their medically complex child provides valuable insight into parents' motivations and behaviors and offers opportunities for support. 5,[10][11][12] We solicited parental insights into how their ''good parent'' definition shapes their medical decision making and interactions with care providers using an online survey tool utilizing both closed-and openended questions. As part of the survey, we asked parents what behaviors on the part of medical professionals foster or impede their ability to achieve their personal ''good parent'' definition.…”
Section: Introductionmentioning
confidence: 99%
“…One of the unique themes was related to validating and reinforcing parental beliefs about having been 'good parents' to their very ill child [12]. The authors of this qualitative study urged for additional inquiry into this revealed 'good parent' theme [13].…”
Section: Introductionmentioning
confidence: 91%